The species of Ormyrus Westwood (Hymenoptera: Ormyridae) in Iran with description of an unusual new species - Lotfalizadeh, Hosseinali; Askew, Richard R.; Fuentes-Utrilla, Pablo; Tavakoli, Majid (Zootaxa, 2012)
An account is given of the Iranian species of Ormyrus Westwood (Hymenoptera: Chalcidoidea: Ormyridae). Eleven species arelisted from Iran, including Ormyrus pallens Lotfalizadeh & Askew n. sp., and six species that are newly reported from Iran, O.bingoeliensis Doğanlar, O. bucharicus Zerova, O. cupreus Askew, O. diffinis (Fonscolombe), O. discolor Zerova and O.wachtli Mayr. New biological associations for the Iranian species are presented, and geographical distribution and biological data are summarised.